Managerial Skills of School Heads in The Development of Religious Culture in Junior High School Number 9 of Palembang - Sari, Diana Nurma; Harapan, Edi; Wardiah, Dessy (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2021)
This study aims to identify and describe the Managerial Skills of Principals in the development of Religious Culture at junior high school of Palembang. The method used is a qualitative method. Data collection techniques using observation, interviews and documentation. The results of the study concluded that the management of the Principal of junior high school of Palembang in developing a religious culture was through planning, organizing, implementing, monitoring and evaluating. The management carried out by the Principal of junior high school of Palembang includes: first the implementation of daily activities in the form of: giving examples, admonitions / advice, environmental conditioning that supports character education, routine activities / character habituation, and mentoring and supervision of character education. The two management of junior high school of Palembang through programmed activities in the form of: Imtaq activities before starting lessons and Khatam Al-Quran every month, dhuha prayer activities, dzuhur prayers in congregation, Ramadhan Islamic boarding school activities, PHBI activities, joint literacy activities. The three Principal Management of junior high school of Palembang through learning activities. In learning activities, a religious culture must be implemented, which includes planning and learning tools containing religious values